The challenge of the spiral-of-silence theory - Wolfgang Donsbach (Communicare)
This article describes the state-of-the-art of Elisabeth Noelle-Neumann's theory of the dynamics of public opinion processes called the "spiral-of-allence-theory". The theory comprises several single hypotheses which relate to different fields of social sciences behavioral and attitudinal psychology, communication research and social theory. Its core assumption is the hypothesis that in dividuals have a fear of isolating themselves in public situations and thus tend not to ex claim their own opinions when they perceive the majority of their fellow citizens to hold the opposite point of view. Noelle-Neumann's ap proach has been discussed and criticised by scholars from different fields. Nevertheless, the empirical evidence up to now seems to underline that it has the potential to explain some of the variance in individual behaviour and in the dynamics of public opinion pro-V cesses.